Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.5114/aoms.2016.62910
|View full text |Cite
|
Sign up to set email alerts
|

Correlation research between osteoporosis and left ventricular hypertrophy in older men

Abstract: IntroductionThe aim of the study was to correlate between osteoporosis and left ventricular hypertrophy (LVH) in older men.Material and methodsOne hundred and forty-six cases of senile male subjects were selected and divided into a normal bone mineral density group, an osteopenia group, and an osteoporosis group based on bone mineral density (BMD). Detailed history inquiry and clinical examination were used to determine biochemical indicators. Femoral neck BMD and lumbar BMD were determined. Electrocardiograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Epidemiological studies [ 8 ] also showed that osteoporosis and osteopenia were risk factors for cardiovascular disease or atherosclerosis disease. In the general female population and older men, BMD was shown to be an independent factor determining LVMI [ 9 , 10 ]. In the study by Hisashi et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies [ 8 ] also showed that osteoporosis and osteopenia were risk factors for cardiovascular disease or atherosclerosis disease. In the general female population and older men, BMD was shown to be an independent factor determining LVMI [ 9 , 10 ]. In the study by Hisashi et al.…”
Section: Discussionmentioning
confidence: 99%
“…For the non-CKD population, a close relationship has been observed between cardiovascular disease and osteoporosis [ 8 ]. Bone mineral density (BMD) has been demonstrated to be an independent determinant of LVMI in the general population [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…There may be a correlation between the osteoporosis and other diseases such as left ventricular hypertrophy (LVH) [17].…”
Section: Discussionmentioning
confidence: 99%
“…There may be a correlation between osteoporosis and other diseases such as left ventricular hypertrophy (LVH) [ 17 ]. Osteoporosis mainly results from an imbalance between osteoblastogenesis and osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%